Management Information System Web-Base on Blood Donation Service - Suartini, Sri; Ikhwan, Ali (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Blood donation is an activity of sharing blood from a person to others in need. This activity was carried out because of the large number of patients in the hospital who needed blood for their illness. The amount of blood needed is not proportional to the amount of blood stock in the hospital, so it is deficient and requires a lot of blood from donors. The scarcity of blood stocks does not occur only in hospitals but also in PMI (Indonesian Red Cross) so that patients or families have difficulty finding blood to meet the needs of patients. The method used in these crisis conditions is to contact a few random people, or create information on personal social media about who can donate blood. This method is less efficient and effective because the data of potential donors is often also not qualified and data collection is also still done manually by the blood transfusion unit. Information technology is one of the solutions in providing information and data collection as well as management in the blood transfusion unit PMI Deli Serdang. In this case the R&D method ( Research And Development) can help develop a management information system to collect data in blood donation services at PMI Deli Serdang.